The Cyber Footprint of Digital Activism: The Legal Boundary between Freedom of Expression and Hate Speech in Indonesia - Daimah Daimah; Nico Krisch (Indonesian Cyber Law Review, 2025)
The development of digital technology has encouraged the emergence of digital activism as a new means for citizens to voice opinions and fight for socio-political rights. However, in Indonesia, this space for digital expression is often faced with repressive regulations, particularly through the use of rubber articles in the Electronic Information and Transaction Law (ITE Law). This research aims to critically analyze the legal boundary between freedom of expression and hate speech in the context of digital activism, identify potential abuses of digital law against activists and citizens, and offer a just and democratic juridical framework. Using a descriptive qualitative approach with a case study method, data was collected through documentation of legal regulations, interviews with key figures, and netnographic observations on social media. The results show that ITE Law is often used as an instrument to silence political expression, with the trend of reporting against activists increasing in the last four years. The unclear definition of hate speech and the absence of explicit protection for political expression worsen the conditions for digital democracy. This research recommends digital regulatory reforms, including the establishment of an independent oversight body and affirmation of the legal boundary between criticism and hate speech, to guarantee civil rights in the cyber era.